2015
DOI: 10.1080/10402004.2015.1010762
|View full text |Cite
|
Sign up to set email alerts
|

Design of Spur Gears Using Profile Modification

Abstract: In this work, a profile modification technique was used in design of a spur gear. In this technique, the tooth-sum is varied to obtain the desired contact ratio and low contact stress for a specified center distance. A program has been developed using C language to compute the contact stresses by varying the amount of profile shift for a tooth-sum of 100 teeth ( §4%). The selected tooth-sum of 96, 100, and 104 gears was subjected to cyclic loading using a back-to-back test rig. The morphology of the damaged ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The scanning electron microphotographs are taken at pitch circle area. The morphological results of points B (LPSTC) and D (HPSTC) were studied and published earlier by the authors . According to that, as per the consideration of only contact stress, points B (LPSTC) and D (HPSTC) are critical.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scanning electron microphotographs are taken at pitch circle area. The morphological results of points B (LPSTC) and D (HPSTC) were studied and published earlier by the authors . According to that, as per the consideration of only contact stress, points B (LPSTC) and D (HPSTC) are critical.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the authors have shown the shifting of maximum contact stresses along the length of contact for various profile shifts [19][20][21] for a tooth sum of 100 (altered by ±4% with a standard centre distance and gear ratio of 1 : 1), but the effect of sliding velocity has not been taken into consideration in previous studies. In view of this research gap, the (σ V s ) factor has been analysed in this investigation for tooth sum for various profile shifts mentioned in the preceding texts.…”
Section: Estimation Of Contact Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In order to improve the quality of gear meshing, tooth surfaces with different orders of transmission errors are obtained by gear profile modification technique. [2][3][4] Experimentation and practice show that gear transmission system with higher order polynomial function of transmission error (H-TE) has lower vibration, better noise performance, and more reliable stability compared to the second-order parabolic function of transmission error (2-TE) system. Due to the interference in the machining process when tooth surface with higher order transmission error than sixth-order polynomial function of transmission error (6H-TE), tooth surface with 6H-TE was selected as the study object.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, conducting simulations and evaluating the performance of the gear pair with tooth profile modification are difficult. Sachidananda et al [14] proposed a method to calculate the contact stress of the modified gear pair. However, this method is not suitable for calculating the bending stress.…”
Section: State Of the Artmentioning
confidence: 99%